Dangerous affair - Owens, Sandra (Harlequin romantic suspense, 2025)
"Protecting her is his mission. Failure is unacceptable. World-traveling photojournalist Quinn Sullivan is stopped in her tracks when a kidnapper holds her captive in a mountain cabin. Could it be related to the damning evidence she has about a company's illegal tactics that are harming a town? To her rescue comes former marine ranger Liam O'Rourke. His assignment as a bodyguard keeps him close to Quinn, protecting her from ongoing threats. Much to his frustration, Quinn does flings, not relationships; she believes men can't handle her career. But the shared danger of exposing a conspiracy may change their romantic boundaries."--back cover.